2005
DOI: 10.1155/ijrm.2005.202
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Optimum Clocking Position in a Two‐Stage Axial Turbine

Abstract: A frozen rotor approach in a steady calculation and a sliding mesh approach in an unsteady simulation are performed in a stator clocking investigation. The clocking is executed on the second stator in a two-stage axial turbine over several circumferential positions. Flow field distributions as well as the estimated performances from two approaches are compared with each other. The optimum clocking positions are predicted based on the estimated efficiency from the two approaches. The consistence of the optimum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Hence, the effect of the relative angle between the front and rear rotor was negligible, and the 0 • relative angle was considered for further simulations to evaluate the aerodynamic performance of the counter-rotating ducted fan. Similar relative angle studies conducted in a gas turbine pre-swirl system [24], an axial turbine [25], and a centrifugal pump [26] also concluded that the effect of the relative angle is negligible.…”
Section: Effect Of Relative Angle Between Front and Rear Rotormentioning
confidence: 67%
“…Hence, the effect of the relative angle between the front and rear rotor was negligible, and the 0 • relative angle was considered for further simulations to evaluate the aerodynamic performance of the counter-rotating ducted fan. Similar relative angle studies conducted in a gas turbine pre-swirl system [24], an axial turbine [25], and a centrifugal pump [26] also concluded that the effect of the relative angle is negligible.…”
Section: Effect Of Relative Angle Between Front and Rear Rotormentioning
confidence: 67%
“…The first-stage vane is rotated by 0.21 deg while the blade is rotated by 0.1 deg in order to sweep these two angular periods. According to Bohn et al (2005), the steady simulation of the clocking phenomena adopting the frozen rotor method has allowed determining the proper optimal clocking position in a multistage axial turbine. In addition, the unsteady simulation of all the stator-stator clocking positions was not possible due to the enormous computational time and the limitation of the computation resources.…”
Section: Clocking Effectsmentioning
confidence: 99%
“…[1][2][3] Clocking effect was previously found in compressors and turbines. Researchers like Bohn, 4 Key, 5 and Schennach 6 studied the clocking effect in turbine and compressor to reveal the flow behavior variance in internal flow field and influence rules of clocking effect on aerodynamic performance. Thereafter, published research works show there also exist clocking effect in centrifugal pumps with vane diffuser and they expound head, efficiency and pressure fluctuation changing with different diffuser-tongue position.…”
Section: Introductionmentioning
confidence: 99%